2019
DOI: 10.15446/abc.v24n3.79367
|View full text |Cite
|
Sign up to set email alerts
|

Primer reporte de begomovirus infectando cultivos de ají (<i>Capsicum</i> spp.) en Colombia

Abstract: Virus del género Begomovirus infectan cultivos de importancia económica en todo el mundo, incluyendo ají. A la fecha, en Colombia no hay reportes de la presencia de begomovirus infectando este cultivo, por lo que el objetivo de esta investigación fue identificar la presencia de virus de este género en ají empleando estrategias moleculares. Se colectaron 197 muestras de ají en diez municipios del Valle del Cauca. Se extrajo el DNA genómico total vegetal y mediante PCR se detectó la presencia de begomovirus. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Only the presence of a potyvirus, the pepper deforming mosaic virus (PepDMV) (Morales et al, 2005) and recently, a begomovirus (Vaca-Vaca et al, 2019) have been reported as presently affecting these crops. The cucumber mosaic virus (CMV) has only been detected using serological techniques like ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Only the presence of a potyvirus, the pepper deforming mosaic virus (PepDMV) (Morales et al, 2005) and recently, a begomovirus (Vaca-Vaca et al, 2019) have been reported as presently affecting these crops. The cucumber mosaic virus (CMV) has only been detected using serological techniques like ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new begomovirus was detected in chili peppers (Capsicum spp.) in Valle del Cauca but its identity is being studied (Vaca-Vaca et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%